A suggestion on analysis and utilization method of motherboard supporting led system - Park, Seil; Jang, Jongwook (International Journal of Engineering and Technology, 2018)
The most popular technology trend for desktop PC motherboard makers in recent years is the mounting of LED systems on motherboards. Motherboard LED system refers to the integrated control of LEDs of various desktop custom parts such as CPU cooler, RAM, graphic card, system cooler connected to the motherboard. In the case of the initial motherboard LED system, the integrated control of the LED was simply performed to show a cosmetically cool effect. However, the use of various color LEDs as a means of data representation has attracted attention recently. For example, data generated by a motherboard sensor is represented in a motherboard LED system. In other words, it uses LEDs supported by the motherboard to represent the temperature, LAN speed, and CPU usage of the desktop. In this paper, To propose a method to express data such as e-mail, SNS, and stock information through various API interworking to utilize motherboard LED system effectively. The proposed method enables the use of a motherboard LED system to receive notifications of Windows applications on the desktop, such as the push notification technology of smartphones. In particular, the API can be used to provide the necessary data in real time, and it is convenient and stable to process only the notification data. As a result, we can solve the inefficiency of the tuning parts that show only the aesthetic effect through the utilization method of the motherboard LED system proposed in this paper, and it can be very useful in the actual computing environment of the user. And because it can represent any data based on API even if it is not e-mail, SNS, or stock information, the value of motherboard LED system is expected to be unlimited.Â Â